Distribution and abundance of common bottlenose dolphin ( Tursiops truncatus ) over the French Mediterranean continental shelf - Hélène Labach; Caroline Azzinari; Maxime Barbier; Cathy Cesarini; Boris Daniel; Léa David; Frank Dhermain; Nathalie Di‐Méglio; Benjamin Guichard; Julie Jourdan; Valentin Lauret; Nicolas Robert; et al. (Marine Mammal Science, 2022)
The common bottlenose dolphin ( Tursiops truncatus ) subpopulation in the Mediterranean is listed as vulnerable by the International Union for Conservation of Nature. This species is strictly protected in France and the designation of Special Areas of Conservation (SAC) is required under the EU Habitats Directive (92/43/EEC). However, little information is available about the structure and dynamics of bottlenose dolphins in French Mediterranean waters. We collected photo‐identification data over the whole French Mediterranean continental shelf year‐round between 2013 and 2015. We sighted 151 groups of bottlenose dolphins allowing the individual photo‐identification of 766 animals. The encounter rate distribution showed the presence of bottlenose dolphins over the whole continental shelf year‐round. We estimated for the first time, using capture‐recapture methods, the size of this bottlenose dolphin population at 2,350 individuals, 95% credible interval [1,827, 3,135]. Our results were used in support of the designation of a new dedicated SAC in the Gulf of Lion and provide a baseline for the bottlenose dolphin monitoring in the French Mediterranean waters in the context of the Marine Strategy Framework Directive.

Genetic composition, origin and conservation of loggerhead sea turtles (Caretta caretta) frequenting the French Mediterranean coasts - Anaïs Loisier; Marie-Paule Savelli; Véronique Arnal; Françoise Claro; Delphine Gambaiani; Jean Baptiste Sénégas; Cathy Cesarini; Jacques Sacchi; Claude Miaud; Claudine Montgelard (Marine Biology, 2021)